The challenges on the way from socialism to nation-states: the perspective from the political left (KULT_online, 2015)
This edited volume aims to cover a wide range of topics related to Yugoslavia and its successor states. The core themes are the historical analysis of the social conditions and the contradictions of the (post-) Yugoslav society. The main focus in this analysis are the Yugoslav Partisans and the war remembrance on the one hand, and the social movements and protests on the other. The book encompasses a chronological framework from the interwar period, through socialist Yugoslavia, to the current issues, providing new perspectives and posing new questions. The volume consists not only of scholarly contributions, but also assembles a diverse compilation of essays, reports, interviews, and photos.